Ethoxide-Mediated Condensation of γ-tert-Butylallenoate and Aldehydes: Facile Stereoselective Synthesis of Conjugated Dienes and Enynes - Xu, Silong; Wang, Liyi; Tang, Yuhai; He, Zhengjie (Synthesis, 2014)
The condensation reaction of a γ-tert-butylallenoate, ethyl 5,5-dimethylhexa-2,3-dienoate, and aldehydes in the presence of sodium ethoxide is described. A range of aldehydes readily reacts with γ-tert-butylallenoate and ethoxide providing a straightforward synthesis of 1,2,3,4-tetrasubstituted conjugated dienes in moderate to good yields and exclusive E,E selectivity. For some aldehydes, the condensation chemoselectively delivers conjugated enynes in good yields and exclusive E selectivity.
Keywords: conjugated diene; enyne; allenoate; condensation; tandem reaction